2013
DOI: 10.1007/978-3-7091-1434-6_10
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hydrogen Gas on a Mouse Bilateral Common Carotid Artery Occlusion

Abstract: In recent studies, molecular hydrogen selectively reduced the levels of hydroxyl radicals in vitro and exerted a therapeutic anti-oxidant activity in a rat middle cerebral artery occlusion model. The aim of this study was to investigate the effect of hydrogen gas on a mouse bilateral common carotid artery occlusion (BCCAO) model. Male C57BL/6J mice were subjected to transient BCCAO with a nontraumatic aneurysm clip. The mice were divided into three groups: sham, BCCAO, and BCCAO treated with 1.3 % hydrogen gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…Similarly, in another study on hydrogen inhalation therapy, inhalation of 1.3% H2 significantly reduced brain edema in BCCAO mice 24 h after reperfusion. [39] Ischemic brain edema is characterized by cytotoxic effects. Ischemia and hypoxia both lead to the production of cytokines and free radicals, which, in addition to microglial and inflammatory activation, result in cell necrosis and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in another study on hydrogen inhalation therapy, inhalation of 1.3% H2 significantly reduced brain edema in BCCAO mice 24 h after reperfusion. [39] Ischemic brain edema is characterized by cytotoxic effects. Ischemia and hypoxia both lead to the production of cytokines and free radicals, which, in addition to microglial and inflammatory activation, result in cell necrosis and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…[42] In experiments in which inhaled hydrogen was used to treat ischemic-reperfusion in BccAo mice, researchers concluded that the reduction in cerebral edema may be due to hydrogen protecting endothelial cells by reducing oxidative stress. [39] In addition, we examined the expression of the antioxidant enzymes SOD1 and CAT in the hippocampus: the qPCR results showed that the expression of SOD1 and CAT was significantly elevated in the BccAo group, and decreased in both the BccAo+3dMSN and BccAo+7dMSN groups. Most studies have found that antioxidant-related enzyme activities are reduced in acute stroke and ischemia-reperfusion injury; however, oxidative and antioxidant homeostasis is a very complex biological process, and it has also been found that under cerebral hypoxia, due to elevated levels of ROS, the cells may increase the expression and activity of CAT and SOD in order to increase the ability to scavenge hydrogen peroxide, thus protecting cells from oxidative damage.…”
Section: Discussionmentioning
confidence: 99%